Neurodegeneration-Associated Proteins in Human Olfactory Neurons Collected by Nasal Brushing - Brozzetti, Lorenzo; Sacchetto, Luca; Cecchini, Maria Paola; Avesani, Anna; Perra, Daniela; Bongianni, Matilde; Portioli, Corinne; Scupoli, Maria; Ghetti, Bernardino; Monaco, Salvatore; Buffelli, Mario; Zanusso, Gianluigi (Frontiers in Neuroscience, 2020)
The olfactory neuroepithelium is located in the upper vault of the nasal cavity, lying on the olfactory cleft and projecting into the dorsal portion of the superior and middle turbinates beyond the mid-portion of the nasal septum. It is composed by a variety of cell types including olfactory sensory neurons, supporting glial-like cells, microvillar cells and basal stem cells. The neuroepithelium is often intermingled with respiratory and metaplastic epithelial cells, differently from rodents where the olfactory and respiratory epithelia are clearly distinct. Olfactory neurons undergo a constant self-renewal in a time lapse of 2-3 months and are directly exposed to the external environment and liable to physical and chemical injuries which might induce metabolic breakdown and ultimately cell death. However, the lifespan of olfactory neurons is biologically programmed and for this reason these cells have an accelerated metabolic recycle leading to an irreversible apoptosis. These features make them an excellent model for studying neurodegeneration process and neuronal aging. Recently, we showed that a non-invasive and painless olfactory brushing procedure allows an efficient sampling of olfactory neuroepithelium. This approach permitted to detect by Real-Time Quaking Induced Conversion (RT-QuIC) assay the pathologic prion protein in patients with sporadic Creutzfeldt-Jakob disease. The investigation of the expression pattern of other proteins associated to neurodegeneration in the olfactory mucosa cells collected by nasal swab is a brand new-field of study. Our aim was to investigate the expression of proteins involved in neurodegenerative processes in olfactory neurons from healthy subjects. We showed that distinct proteins involved in neurogenerative diseases, including α-syn, APP/β-Amyloid, tau, TDP-43, are expressed in olfactory neurons, so that aggregates deposits observed in the olfactory bulb in early stage of neurodegenerative process may derive from protein misfolding triggered in the olfactory neuroepithelium.